Towards a green school - Moya Contreras, Jesús (Pulso. Revista de educación, 2002)
This article describes the efforts made by a group of students and teachers from Sagrada Familia School in Cartagena to enhance and preserve the environment by adapting the school to eco-friendly practices. The project is a part of the "Green Schools" programme initiated by the City of Cartagena.